ANALYSIS OF THE EFFECTIVENESS, EFFICIENCY, AND CONTRIBUTION OF REGIONAL TAXES IN EFFORTS TO INCREASE REGIONAL ORIGINAL INCOME IN MAGELANG REGENCY 2016-2020 - Shinta Dian Ayu Pitaloka; Ari Nurul Fatimah (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2022)
The study aims to determine the level of efficiency, and local tax levies in an effort to increase Regional Original Income in Magelang Regency for 5 consecutive years, namely 2016, 2017, 2018, 2019, 2020. Regional taxes are a supporting component of Regional Original Income so that it can help increase Regional Original Income. This analysis uses a qualitative descriptive method to determine the level of effectiveness, efficiency, and contribution of local taxes in a effort to increase Regional Original Income in Magelang Regency. The data used is secondary data obtained from the Badan Pendapatan, Pengelolaan Keuangan dan Aset Daerah of Magelang Regency. The result of the analysis reveal that the effectiveness of local taxes for 5 consecutive years is declared very effective, efficiency of local taxes is declared very efficient, and the contribution of local taxes is stated to be quite good at the level of contribution.